Prevalence and Predictors of Obesity among 7- to 17-Year-Old Schoolchildren in Urban Arusha, Tanzania - Haji Chomba; Haikael D. Martin; Judith Kimywe (Journal of Nutrition and Metabolism)
Background. Childhood obesity is currently increasing at an alarming rate worldwide. Childhood obesity research has not been reported in urban Arusha before. This is therefore the first study to investigate the prevalence and predictors of childhood obesity in urban Arusha. Methods. A cross-sectional study was conducted involving 451 schoolchildren. Overweight was defined to range from 85th to 94th BMI percentile for age and sex while obesity was defined as above 94th BMI percentile for age and sex. Chi-square test was used for comparison between child sex and sociobehaviors, and multiple logistic regression was used to determine the significant predictor factors at P values = 0.05. Results. The overall prevalence of overweight and obesity was 17.7% (80/451) with 12.6% (57/451) being obese and 5.1% (23/451) being overweight. Results from univariate logistic regression showed child sex, random sleeping time, and random eating habit were the significant predictor factors. However, when all the predictor factors were used in the final multiple logistic regression model, only random sleeping time and random eating habit of different food items irrespective of their nature were significant at P=0.000, AOR = 4.47, and 95% CI = 2.00–10.01, and P=0.012, AOR = 2.54, and 95% CI = 1.23–5.33, respectively. Conclusions. The prevalence of obesity was as higher as twice the prevalence observed in other previous studies in Tanzania. Being a girl, random sleeping time and random eating habit were independent predictors. In addition to larger sample sizes, longitudinal studies are needed in order to track individuals and population level trends in BMI over time.